2020
DOI: 10.1088/1757-899x/737/1/012143
|View full text |Cite
|
Sign up to set email alerts
|

Traffic signs comprehension study

Abstract: Current research work investigates road user’s comprehension of different traffic control devices. Sample demographics were taken into consideration such as age, gender, and educational background. Twenty regulatory and warning signs were examined in this study. These signs vary from simple ‘No parking’ sign to more tricky ones such as ‘Divided highway’ sign. In addition, the questionnaire includes other questions related to road safety, condition of roads signs, and feeling of safety as a driver and as a pede… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 2 publications
0
1
0
Order By: Relevance
“…Based on educational background, several research have found that drivers with higher education have significantly better comprehension compared to those with lower educational attainment (Al-Rousan & Umar, 2021;Choocharukul & Sriroongvikrai, 2017). Furthermore, Abduljabbar et al (2020) reported that the higher the driving experience, the better the ability to understand traffic signs. Another factor that affects signs comprehension is gender, where male drivers have a better level of signs comprehension compared to their female counterparts (Taamneh, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Based on educational background, several research have found that drivers with higher education have significantly better comprehension compared to those with lower educational attainment (Al-Rousan & Umar, 2021;Choocharukul & Sriroongvikrai, 2017). Furthermore, Abduljabbar et al (2020) reported that the higher the driving experience, the better the ability to understand traffic signs. Another factor that affects signs comprehension is gender, where male drivers have a better level of signs comprehension compared to their female counterparts (Taamneh, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Comprehension of traffic signs may consider human characteristics of the drivers, ergonomic principles, cognitive features and the cultural issues (Ishartomo et al, 2020). Familiarity with signs can help drivers understand their meaning (Abduljabbar et al, 2020), but familiarity is not always linear with comprehensibility. Drivers who are familiar with certain signs do not always understand their meaning (Akple et al, 2020).…”
Section: Introductionmentioning
confidence: 99%